Associations between follicular fluid and serum neonicotinoid insecticide exposure and sex hormones and ovarian reserve: A retrospective study among women undergoing IVF/ICSI - Nijie Li; Ziyu Liu; Linan Xu; Rui Huang; Zhenhan Xu; Guihua Liu; Xing Yang; Xiaoyan Liang (Ecotoxicology and Environmental Safety, 2025)
Widespread utilization of neonicotinoid insecticides (NNIs) has led to their infiltration into the human body, resulting in their detrimental effects on human health. To date, studies on the impact of NNI exposure levels on the female reproductive endocrine system are limited. To address this, we aimed to explore the impact of exposure to NNIs in the environment on ovarian reserve and sex hormones to investigate potential endocrine-mediated reproductive toxicity. Using liquid chromatography–tandem mass spectrometry, we collected and analyzed fifteen kinds of NNIs in 436 paired serum and follicular fluid samples from women undergoing IVF/ICSI, who were recruited in southern China. Linear regression model and BKMR model were applied to explore the associations between NNIs exposure and sex hormones and ovarian reserve. We found that NNIs exposure was associated with alterations of sex hormones and decrease of ovarian reserve, suggesting endocrine disrupting effects of NNIs. Our study provides evidence that environmental exposure to NNIs may disrupt the functional dynamics of hypothalamus-pituitary-ovary (H-P-O) axis regulation in women undergoing IVF/ICSI.